PEMANFAATAN TEKNOLOGI DALAM MENDORONG JIWA BERWIRAUSAHA DI ERA SOCIETY 5.0 - Azis, Muhammad; Waliyullah, Akbar; Azis, Fajriani; Rusdi, Nur Risma; Ashari, Elza Rahayu; Munawarah, Nita Madinatul; Arwadi, Fajar (Jurnal Pengabdian Masyarakat Sabangka, 2023)
The rapid advancement of information technology, particularly the internet, has had a significant impact on various aspects, including business and marketing. Nowadays, numerous companies and individuals utilize the internet as a platform for marketing and conducting business. Consequently, this trend influences the purchasing behavior of individuals within the community, as they rely on the internet to fulfill their goods and services needs. To address this evolving landscape, the KKNT UNM Team in Lerang Village organized an Entrepreneurship Seminar aimed at young people and parents. The purpose of this seminar was to promote entrepreneurship and establish better communication and camaraderie among the Lerang Village community. It served as a platform to revitalize the entrepreneurial spirit in the era of Society 5.0. The seminar, titled "Utilizing Technology to Foster Entrepreneurial Spirit," took place at MI DDI Kaloang, a venue capable of accommodating a large audience. The event primarily attracted young individuals and the elderly from Lerang Village.